2022
DOI: 10.1021/acs.iecr.1c04654
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Properties of Polyimide/Carbon Fiber Aerogel and the Derivative Carbon Aerogel

Abstract: In this study, polyimide (PI)/carbon fiber (CF) aerogel was fabricated via a freeze-drying method. The introduction of CF endows PI aerogels with good dimensional stability in the thermal imidization process. The resulting aerogel possesses excellent mechanical property (as high as 58.45 MPa) and good hydrophobic property (contact angle above 120°). The PI/CF aerogel also has very good radiation resistance, with a compressive modulus of 50.45 MPa even after 10 MGy irradiation, which is 86.53% of the initial mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The integration of exibility and high-temperature thermal stability made this material superior to state-of-the-art reports on PI-based composites. 7,8,30,31 Additionally, a nite-element model was set up to investigate the temperature distribution and the recession transition. To the best of our knowledge, there are few reports about bre-reinforced resin composites possessing both reversible deformability and thermal protection performance at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of exibility and high-temperature thermal stability made this material superior to state-of-the-art reports on PI-based composites. 7,8,30,31 Additionally, a nite-element model was set up to investigate the temperature distribution and the recession transition. To the best of our knowledge, there are few reports about bre-reinforced resin composites possessing both reversible deformability and thermal protection performance at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest thermal conductivity of PI/carbon fiber composite aerogel obtained by freeze drying and carbonization is 48 mW m −1 K −1 ; the thermal conductivity of SiO 2 /PI composite aerogel with a layered porous structure prepared by the co-gel method is only 31.10 mW m −1 K −1 ; and the high-porosity hydroxyapatite/PI composite aerogel achieved a low thermal conductivity of 32.21 mW m −1 K −1 . 6,24,43 Therefore, the thermal insulation performance of PI/TPU-0.5 is at a high level. However, the thermal conductivity of T-PI is not ideal as a result of its density, which is significantly higher than that of pure PI and PI/TPU-0.5 (Table 2), and its relatively low porosity, which shortens the air flow conduction path.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Usually, the thermal imidization is carried out at a high temperature of 200–300 °C, which inevitably leads to the collapse and severe shrinkage of the aerogel structure, while the dehydration and cyclization process in the chemical imidization occurs at a low temperature; therefore, the latter is more preferable for maintaining the integrity of aerogel. Freeze drying provides advantages over supercritical drying in terms of environmental protection, ease of use, low cost, and conditional mildness …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, some studies have suggested that the above problem can be reduced by adding inorganic fillers into the matrix. 23 Because of its remarkable mechanical, electrical, and thermal properties, graphene has been used to modify polymer composite materials. As one of its derivatives, graphene oxide (GO) not only inherits the advantages of graphene, but also shows good dispersity in polymers due to the rich oxygen-containing functional groups on its surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the process of thermal imidization and carbonization, PI aerogels may undergo serious shrinkage, which is unfavorable to obtaining a low density and the desirable structure. Fortunately, some studies have suggested that the above problem can be reduced by adding inorganic fillers into the matrix . Because of its remarkable mechanical, electrical, and thermal properties, graphene has been used to modify polymer composite materials.…”
Section: Introductionmentioning
confidence: 99%